MANAJEMEN RISIKO KEHILANGAN PANEN EDAMAME (Glycine max (L) Merr.) DI PT. MITRATANI DUA TUJUH, JEMBER - Yuli Wibowo; Winda Amilia; Dyah Rizki Karismasari (JURNAL AGROTEKNOLOGI, 2020)
Post-harvest loss is a risk that can be faced by almost all agricultural commodities, including edamame. Post-harvest loss can be a potential loss for farming. This study aims to identify the risk of edamame post-harvest loss at PT. Mitra Tani Dua Tujuh Jember, as well as formulating its control strategy. This study uses the Failure Mode and Effect Analysis method to analyze the risk of post-harvest loss, integrated with the fishbone diagram to identify the risk causes. To formulate a risk control strategy used the Analytical Hierarchy Process method, which refers to the Pugh method to determine the strategic concept. The results showed that the most critical risks that need serious attention in edamame production are the emergence of pests and diseases. Pests and diseases that attack edamame plants have a high impact severity. Pests and diseases quite often attack edamame plants, and their presence is difficult to detect. The appropriate strategy for controlling pests and diseases in edamame is vegetable pesticides. The use of vegetable pesticides is easier, more efficient, cheaper, more effective, and easier to obtain than chemical pesticides. Keywords: analytical hierarchy process, edamame, failure mode and effect analysis, post-harvest loss, risk management